Unusual presentation of occipital condyle fracture: Contralateral hypoglossal nerve palsy - Inci, Mehmet F.; Demir, Caner F.; Ozkan, Fuat; Yildiz, Mustafa (Medknow Publications & Media Pvt Ltd, 2012)
[Abstract Not Available]
Keywords: Head Trauma; Injury; Ct; Paralysis